Individualized Compensation of Anterior Segment Birefringence during Scanning Laser Polarimetry - Zhou, Qienyuan; Weinreb, Robert N (Investigative ophthalmology & visual science, 2002)
To describe a method for assessment and individualized compensation of anterior segment birefringence with scanning laser polarimetry. A scanning laser polarimeter (GDx Nerve Fiber Analyzer; Laser Diagnostic Technologies, Inc., San Diego, CA) was modified to accommodate a variable compensator. The magnitude and axis of anterior segment birefringence of normal eyes were determined from a polarimetry image of the Henle fiber layer. The variable compensator was then adjusted to minimize anterior segment birefringence. Retinal nerve fiber layer (RNFL) and macular measurements were then obtained. Macular images with individualized compensation served to verify the effectiveness of the compensation. To demonstrate individualized compensation, two sets of three images each were obtained from four eyes of four normal subjects. One set was obtained with individualized compensation and another with fixed compensation, as used in the commercial polarimetry system. In the tested eyes, the magnitude of anterior segment birefringence ranged from 21.7 to 86.3 nm, and the slow axis ranged from 5.7 degrees nasally upward to 54.3 degrees nasally downward. The maximum residual retardation resulting from compensation was 70 nm for fixed compensation and 11.5 nm for individualized compensation. The compensation residual directly affected the assessment of the RNFL by scanning laser polarimetry. RNFL images obtained with individualized compensation were more consistent with the expected anatomy of the eye. In the eyes measured, the range of RNFL thicknesses appeared to be narrower with the variable corneal and lens compensator (VCC) compared with the fixed corneal compensator (FCC). In eyes with a normal macula, the magnitude and axis of anterior segment birefringence can be determined from a polarimetry image of the Henle fiber layer. Individualized anterior segment compensation can be achieved with the described method so that the measured birefringence largely reflects the RNFL birefringence. Whether and how macular diseases affect this method remain to be investigated.